2011
DOI: 10.1111/j.1365-2788.2011.01439.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of living arrangements and deinstitutionalisation in the health status of persons with intellectual disability in Europe

Abstract: Background Despite progress in the process of deinstitutionalisation, very little is known about the health conditions of people with intellectual disability (PWID) who live in large institutions and PWID living in small residential services, family homes or independent living within the community. Furthermore, there are no international comparison studies at European level of the health status and health risk factors of PWID living in fully staffed residential services with formal support and care compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 45 publications
1
36
0
1
Order By: Relevance
“…Previous research, findings are consistent with the results presented here: residence patients are significantly older than those living in community settings, 26,28,29 are affected by more severe levels of IDD 28 and are more likely to suffer from mental health problems and behavioral disorders. 28,29 In this sense, recent literature shows that people with IDD have a higher risk of developing comorbid psychopathology, and their symptoms remain relatively stable over time.…”
Section: Comparison With Other Studiessupporting
confidence: 82%
See 1 more Smart Citation
“…Previous research, findings are consistent with the results presented here: residence patients are significantly older than those living in community settings, 26,28,29 are affected by more severe levels of IDD 28 and are more likely to suffer from mental health problems and behavioral disorders. 28,29 In this sense, recent literature shows that people with IDD have a higher risk of developing comorbid psychopathology, and their symptoms remain relatively stable over time.…”
Section: Comparison With Other Studiessupporting
confidence: 82%
“…26,27 Similarly, subjects with more severe levels of IDD often dwell at residence institutions and have a higher risk of diseases like epilepsy, mobility issues, mental health problems and behaviour disorders. 28 Besides presenting more severe levels of IDD, mental health issues and behaviour disorders, the population living in institutions has a higher mean age than their peers living in family households, and often leads a more sedentary life. 26,29 All these studies reflect the influence of variables like the severity of the IDD, ageing and institutionalization on the health status.…”
Section: Health In Intellectual Developmental Disordersmentioning
confidence: 99%
“…Four of these articles 90,[102][103][104] reported findings from the same study and a further two articles 109,125 reported findings from the same study, leaving 58 studies (see Table 3) remaining for the final systematic review and meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%
“…Este mismo estudio concluye que se necesitan al menos 134 psiquiatras y psicólogos especializados y 277 camas en servicios especializados para cumplir con los estándares de atención necesarios. 53 Una de las limitaciones más importantes para la correcta atención de las personas con TDI es la falta de formación al respecto de los profesionales sanitarios. En el ámbito europeo, los contenidos relacionados con el TDI en los programas formativos de los profesionales sanitarios son mínimos; las publicaciones sobre la formación y el entrenamiento de profesionales son igualmente escasas.…”
Section: Discussionunclassified